Relative bioavailability and pharmacokinetic study of two trimetazidine modified release formulations in healthy Bangladeshi male volunteers - Islam Chowdhury, Md Mazharul; Ullah, Md Ashik; Iqbal, Naushin; Maruf, Al Abdullah; Shohag, Md Hasanuzzaman; Harun, Saima; Akter, Khondker Ayesha; Begum, Bilkis; Latif, AHM Mahbub; Hasnat, Abul (Arzneimittelforschung, 2011)
Trimetazidine (CAS 5011-34-7) is an effective and well-tolerated antianginal drug that possesses protective properties against ischemia-induced heart injury. The relative bioavailability and pharmacokinetic characteristics of two modified release formulations of 35 mg trimetazidine, one as the test product (Metacard MR) and one as the reference product, were compared in healthy Bangladeshi male volunteers. The randomized, two-way crossover study was conducted in 24 healthy male volunteers after administration of a single 35 mg dose of each modified release formulation after 12-h overnight fasting, with a washout period of two weeks. Blood samples were collected at various time intervals following oral administration and analyzed for trimetazidine concentrations using a validated HPLC method. The pharmacokinetic parameters were determined by a non-compartmental method. After administering a single dose of 35 mg of each trimetazidine formulation, the obtained mean (SD) values for the test and reference products were 104.78 (29.3) and 98.57 (28.7) ng/ml for Cmax; 4.00 (1.1) and 3.54 (1.32) h for tmax; 423.81 (173.9) and 410.01 (195.87) ng · h/ml for AUC0–12; and 472.51 (195.2) and 462.78 (225.13) ng · h/ml for AUCo–∞ respectively. The mean t1/2 was found 3.69 (1.1) h and 3.45 (0.72) h for test and reference products respectively. From paired t-test, no significant differences were observed (p > 0.05) for any pharmacokinetic parameters. The 90% confidence intervals of the test/reference mean ratios of the In-transformed AUC0–12, AUC0–∞ and Cmax mean values were 106.19% (97.16%–116.06%), 104.74% (95.04%–115.42%) and 106.30% (95.23%–118.66%), respectively. The two formulations demonstrated similar bioavailability with respect to both the rate and extent of trimetazidine absorption.
Keywords: Anti-anginal drug; Bangladeshi volunteers; Pharmacokinetics; Relative bioavailability; Trimetazidine